We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is (x^2)/(A^2)-(y^2)/(B^2)=1

where A =_____

B =_____

Guest Jun 16, 2015

#2**+10 **

**Thanks for your excellent answer Heureka.**

I just want to practice this for myself because I keep forgetting it.

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is

$$\frac{x^2}{A^2}-\frac{y^2}{B^2}=1$$

Vertex =( 0 $$\pm$$ A, 0) So A= 4

$$\\Focus=(0\pm \sqrt{A^2+B^2},0)\\\\

\sqrt{16+B^2}=5\\

4^2+B^2=5^2\\

B=3$$

$$\frac{x^2}{4^2}-\frac{y^2}{3^2}=1$$

Melody Jun 16, 2015

#1**+10 **

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is (x^2)/(A^2)-(y^2)/(B^2)=1

$$\dfrac{x^2}{A^2}-\dfrac{y^2}{B^2}=1$$

vertex at (-4 , 0 ):

$$\small{\text{$ \begin{array}{l} (-4,0) =(\pm A ,0)\\ A = \pm4 \end{array} $}}$$

focus at (5 , 0) :

$$\small{\text{$ \begin{array}{l} (5,0) =(\pm \sqrt{A^2+B^2} ,0)\end{array} $}}\\ \begin{array}{rcl} A^2+B^2 &=& 5^2 = 25\\

(\pm4)^2+B^2 &=& 25\\

B^2 &=& 25-16 = 9\\ B &=& \pm 3

\end{array} $}}$$

A = $$\small{\text{$\pm 4$}}$$

B = $$\small{\text{$\pm 3$}}$$

$$\dfrac{x^2}{(\pm 4)^2}-\dfrac{y^2}{(\pm 3)^2}=1$$

heureka Jun 16, 2015

#2**+10 **

Best Answer

**Thanks for your excellent answer Heureka.**

I just want to practice this for myself because I keep forgetting it.

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is

$$\frac{x^2}{A^2}-\frac{y^2}{B^2}=1$$

Vertex =( 0 $$\pm$$ A, 0) So A= 4

$$\\Focus=(0\pm \sqrt{A^2+B^2},0)\\\\

\sqrt{16+B^2}=5\\

4^2+B^2=5^2\\

B=3$$

$$\frac{x^2}{4^2}-\frac{y^2}{3^2}=1$$

Melody Jun 16, 2015